Resolusi Konflik Talak di Luar Pengadilan Perspektif Hukum Islam dan Hukum Positif - Pitria, Ana; Rahman, Fuad; Ramlah, Ramlah (Journal of Comprehensive Islamic Studies, 2023)
This article reveals that the implementation of divorce outside the Religious Courts carried out by the people of Bathin II Babeko District, Bungo Regency, is allegedly not in accordance with the regulations set by the government for people to carry out divorces in front of a court hearing. This article comes from qualitative research using data collection methods through observation, interviews and documentation. Research findings show that the implementation of divorce outside the Religious Courts by the people of Bathin II Babeko District was witnessed by religious figures and the families concerned and some were not witnessed by anyone. While the guarantee of child support is usually with the father, there are also some who do not receive their rights because their husband remarries, or goes abroad and is irresponsible. The response of religious leaders and local sharia officials stated that divorce carried out outside of court has two legal positions; valid according to religious law but not valid according to state law. Artikel ini mengungkap pelaksanaan perceraian di luar Pengadilan Agama yang di lakukan oleh masyarakat Kecamatan Bathin II Babeko Kabupaten Bungo yang disinyalir tidak sesuai dengan peraturan yang telah ditetapkan pemerintah agar masyarakat melaksanakan perceraian di depan sidang pengadilan. Artikel ini berasal dari penelitian kualitatif dengan menggunakan metode pengumpulan data secara observasi, wawancara dan dokumentasi. Temuan penelitian menunjukkan bahwa pelaksanaan perceraian di luar Pengadilan Agama oleh masyarakat Kecamatan Bathin II Babeko disaksikan oleh tokoh agama dan pihak keluarga yang bersangkutan dan ada pula yang tidak disaksikan  oleh siapapun. Sedangkan jaminan nafkah anak biasanya berada pada ayah, namun ada juga beberapa dari mereka yang tidak mendapatkan haknya dikarenakan sang suami menikah lagi, ataupun pergi merantau dan tidak bertanggung jawab. Respon tokoh agama dan pegawai syara’ setempat menyatakan bahwa perceraian yang dilakukan di luar pengadilan mempunyai dua kedudukan hukum; sah secara hukum agama akan tetapi tidak sah secara hukum Negara.